The giardial VPS35 retromer subunit is necessary for multimeric complex assembly and interaction with the Vacuolar protein sorting receptor - Miras, Silvana (2013)
The retromer is a pentameric protein complex that mediates the retrograde transport of acid hydrolase receptors between endosomes and the trans-Golgi network and is conserved across all eukaryotes. Unlike other eukaryotes, the endomembrane system of Giardia trophozoite is simple and is composed only of the endoplasmic reticulum and peripheral vesicles (PVs), which may represent an ancient organellar system converging compartments such as early and late endosomes and lysosomes. Sorting and trafficking of membrane proteins and soluble hydrolases from the endoplasmic reticulum to the PVs have been described as specific and conserved but whether the giardial retromer participates in receptor recycling remains elusive. Homologs of the retromer Vacuolar Protein Sorting (Vps35p, Vps26p, and Vps29p) have been identified in this parasite. Cloning the GlVPS35 subunit and antisera production enabled the localization of this protein in the PVs as well as in the cytosol. Tagged expression of the subunits was used to demonstrate their association with membranes, and immunofluorescence confocal laser scanning revealed high degrees of colabeling between the retromer subunits and also with the endoplasmic reticulum and PV compartment markers. Protein-protein interaction data revealed interaction between the subunits of GlVPS35 and the cytosolic domain of the hydrolase receptor GlVps. Altogether our data provide original information on the molecular interactions that mediate assembly of the cargo-selective retromer subcomplex and its involvement in the recycling of the acid hydrolase receptor in this parasite.